Preference of First Year Medical Students Regarding Theory Teaching Aids and Opinion on Teacher-Student Interaction - S K Kabra; Shreyashkumar J Gandhi (Medsci Publications, 2017)
Introduction: There seems lack of consensus as to best theory teaching aids for Medical Students as brought out during informal discussions with faculty and students. Aims and objectives: The study was conducted to determine the preference of first year Medical Students about theory teaching aids between Black Board and Power Point Presentation and to ascertain opinion on teacher-student interaction. Methodology: A cross sectional study was conducted in two phases, first was from April to August 2015 for 2014 MBBS batch and second was from Jan to Feb 2016 for 2015 MBBS batch. Theory classes were conducted with the use of Black Board and Power Point. A questionnaire was administered. Analysis was done on 5 point Likert scale Results: In the first phase, 69.04% of students preferred Black Board teaching while in the second phase, 66.94% of students preferred Power Point teaching. In first phase 43.65% students and in second phase 64.40% students rated interaction by teacher during theory lectures more than 3 on Likert scale. Conclusion: Preference for Power Point Presentation was statistically highly significant (P < 0.001). So, it can be inferred that Power Point Presentation is preferred by students over Black Board.